Effect of Glycerin Addition On Physical And Mechanical Properties in the Manufacturing Of Biodegradable Plastics From Cassava Skin Strach - Muhrinsyah Fatimura; Rully Masriatini; Denny Irawan (Program Studi Teknik Kimia, Universitas Pamulang, 2023)
Biodegradable plastic is a plastic that is easily decomposed with the help of micro-organism activity. The manufacture of biodegradable plastic in this study used cassava peel starch as raw material, cornstarch as chitosan and glycerin as a plasticizer. The materials used in this study have different composition variations, in cassava peel starch 10 grams in all samples, in cornstarch chitosan using 1 gram in all samples while the glycerin plasticizer uses volume variations of 0.5 ml, 1 ml, 1 ,5ml, 2ml and 2.5ml. The purpose of this study was to determine the characteristics of the mechanical properties of tensile strength, elongation, water absorption and biodegradation of the obtained biodegradable plastic. In each of the tests carried out, the best value was obtained, namely the characteristic value of the biodegradable plastic produced, namely the best tensile strength test results were 0.20491 Mpa at the addition of 0.5 ml glycerin, the best elongation test was 10.90909% at the addition of 2, 5 ml of glycerin, the best water absorption test was 44.62% with the addition of 0.5 ml of glycerin and the best biodegradation test was 0.1275 grams/day on the addition of 0.5 ml of glycerin.